RESCHEDULING FOR JSSP AND FJSSP USING CLONAL SELECTION PRINCIPLE APPROACH – A THEORY - Ahmad Shahrizal Muhamad; Safaai Deris (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2016)
This article was discussed about rescheduling technique for the job-shop scheduling problem and flexible job-shop scheduling problem by using clonal selection principle approach. Job-shop and flexible job-shop scheduling problems are one of the most frequently encountered and hardest to optimize. This article begins with a short brief about scheduling and production scheduling in the dynamic environment. There are two main causes that required for rescheduling process included machine breakdown factor and new job arrival factor. This article will be discussed for this two factor and suggest the several technique for rescheduling process